Enhancing academic conferences with AI: defining the role of the human AI editor - Galan-Cubillo, Esteban; Saez-Soro, Emilio (Institute of Advanced Engineering and Science, 2025)
Academic conferences serve as key platforms for knowledge exchange, yet they face challenges in managing large volumes of content efficiently while maintaining academic rigor. To address these challenges, this study introduces and evaluates the